PERAN STRATEGI DEEP LEARNING DALAM MENINGKATKAN KEAKTIFAN SISWA PADA PROSES PEMBELAJARAN DI MTS HUMAIRA' KOTA BENGKULU - Deby Ansori; Ami Roniza; Elsa Wijayanti; Anna Nuraini; Triency Oktavia; Anggi Rahmadani (PT. Saha Kreasi Indonesia, 2025)
This study aims to describe the role of the deep learning strategy in increasing student activeness in the learning process at MTs Humaira’ Kota Bengkulu. The research was motivated by the low level of student participation in classroom activities, such as asking questions, engaging in discussions, and expressing opinions, which is influenced by the dominant use of lecture-based teaching methods. This study employed a descriptive qualitative method with data collected through participatory observation, in-depth interviews, and documentation. Data were analyzed using the Miles & Huberman interactive model, consisting of data reduction, data display, and conclusion drawing. The findings indicate that the implementation of deep learning covering the stages of exploration, interpretation, decision-making, and reflection significantly enhances students’ activeness. Students become more confident in expressing ideas, more active in asking questions, and more involved in group discussions. Learning also becomes more meaningful through project activities, reflective tasks, and the use of stimulating questions. Challenges such as differences in students’ initial abilities and limited learning facilities can be addressed through scaffolding, the use of simple instructional media, and strengthening the role of teachers as facilitators. This study concludes that the deep learning strategy is effective for fostering student activeness at the MTs level and aligns with the demands of 21st-century learning.